'The Biggest Charity You've Never Heard of': Institutional Logics of Charity and the State in Public Fundraising in Scotland's NHS. (27th April 2023) - STEWART, ELLEN; DODWORTH, KATHY
Abstract: The boundaries between state and charitable activities within the NHS are set out in regulations but are also enacted, blurred, and contested through local practices. This article reports research on NHS Charities– charitable funds set up within NHS organizations to enhance statutory provision – in Scotland. We analysed financial accounts and conducted qualitative interviews with staff in 12 of the 14 NHS Charities in Scotland, where they are generally known as endowments. Our findings suggest that Scotland's endowments are relatively wealthy in charitable terms, but that this wealth is unevenly distributed when population size and socio-economic deprivation are considered. We also identify two diverging organisational approaches to decisions, including those about appropriate and inappropriate fundraising. We argue that these approaches cohere with contrasting 'state' and 'charitable' institutional logics, which in turn imply different attitudes to potential inequalities, and to relationships with local publics.